Effect of thawing and coating of broiler carcass cuts on cooking loss and sensory characteristics - Khalil, Rafea M. T.; Abdelguni, Mohammed Fauzi (Journal of agricultural, environmental and veterinary sciences, 2021)
The object of this experiment to study the effect of thawing and coating of frozen broiler carcass cuts (Breast, thigh, drumstick) on cooking loss percentage and sensory characteristics (Tenderness, flavor, juiciness). 24 carcasses of broiler were divided to the main cuts (Breast, thigh, drumstick) and frozen for 3 weeks then divided to 4 groups of 6 cuts, half of each cuts were thawed on room temperature and the other half left frozen, then half of the thawed and half of the frozen cuts were coated with a layer of Kentucky mix in a plastic bag, then all carcass cuts were fried in deep oil. The results showed that thawing or coating or interaction between them had no significant effect on cooking loss percentage for the three parts, and thawing did not affect sensory characteristics significantly, while coating had a significant effect on tenderness, juiciness, and flavor at (P< 0.05) of the breast and the tenderness of thigh and drumstick (P< 0.05). The interaction between thawing and coating had a significant effect on Juiciness and flavor of breast and tenderness of thigh (P< 0.05) but not significant on drumstick.